Novel Antimicrobial Peptides Bacterial Cellulose Obtained by Symbioses Culture Between Polyhexanide Biguanide (PHMB) and Green Tea - Basmaji, Pierre; Olyveira, Gabriel Molina de [UNESP]; Santos, Marcio Luiz dos [UNESP]; Guastaldi, Antonio Carlos [UNESP] (Amer Scientific Publishers, 2014)
Bacterial cellulose is a highly hydrated pellicle made up of a random assembly of ribbon shaped fibers less than 5 nm wide. The unique properties provided by the nanometric structure have led to a number of diagnostic biological probes, display devices due to their unique size-dependent medical applications. Bacterial cellulose matrix extracellular is a novel biotechnology and unique medicine indicated for ultimate chronic wound treatment management, drug delivery, tissue engineering, skin cancer and offers an actual and effective solution to a serious medical and social problem and to promote rapid healing in lesions caused by Diabetic burns, ulcers of the lower limbs or any other circumstance in which there's epidermal or dermal loss. In this work, it is reported novel antimicrobial peptides (AMPs) bacterial cellulose/polyhexanide biguanide (PHMB) which are produced by symbioses culture between polyhexanide biguanide and green tea culture medium resulting in the pure 3-D structure consisting of an ultra-fine network of novel biocellulose/PHMB nanofibres matrix (2-8 nm), highly hydrated (99% in weight), and with higher molecular weight, full biocompatibility.
Keywords: Bacterial Cellulose (Nanoskin); PHMB (polyhexanide biguanide); Regenerative Medicine; Wound Healing.